De/constructing Literacies: Considerations for Engagement - Lemieux, Amélie (Peter Lang, 2020)
De/constructing Literacies: Considerations for Engagement reviews and defines the concept of engagement in literacy studies from different epistemologies. Well-suited for literacy researchers and graduate students, it considers the foundations of arts-based research, cognitive psychology, ethnography, phenomenology, posthumanism, with a final chapter on walking methodologies, to better understand how engagement can be framed and looked at in literacy studies.

“Back then it was only men who worked in these kind of fields”: Observing little sparks through the prism of affect and gender in maker literacies research. - Lemieux, Amélie (Reading Research Quarterly, 2023)

Porosité et didactique de la littérature au secondaire : Didactisation d’une oeuvre théâtrale et de son adaptation filmique pour un réinvestissement poétique en classe de français - Lemieux, Amélie (La Lettre de l’AIRDF, 2023)

Pour une lecture émancipatoire : bell hooks - Lemieux, Amélie (Revue des sciences de l'éducation, 2022)

M/EDIA/tions: Assises théoriques relatives aux questions d’équité, de diversité, d’inclusion et d’accessibilité (EDIA) pour l’enseignement de la littérature avec le numérique - Lemieux, Amélie (Revue de recherches en littératie médiatique multimodale, 2021)

Antidualisms in maker literacies research: Technological processes, materialities, mappings - Lemieux, Amélie (Education & Didactique, 2021)

What does making produce? Posthuman insights into documenting relationalities in maker education for teachers - Lemieux, Amélie (Professional Development in Education, 2021)

In-class film-viewing for empathy development in higher education - Lemieux, Amélie (Canadian Review of Art Education, 2017)

Moments de réception en lecture et en spectature : Le cas d’Incendies au CEGEP - Lemieux, Amélie (Revue de recherches en littératie médiatique multimodale, 2016)

Think it through: Fostering aesthetic experiences to raise interest in literature at the high school level - Lemieux, Amélie (Journal of the Canadian Association for Curriculum Studies, 2015)

Vers une documentation d'oeuvres littéraires numériques queer - Lescouet, Emmanuelle; Vallières, Amélie; Lemieux, Amélie (BD, Littératie et créations numériques : Quels enjeux pour demain?, 2023)

Approches transactionnelle, subjective, et phénoménologique en didactique de la lecture - Lemieux, Amélie; Lacelle, Nathalie (Myriades, 2016)

Mobilizing subjective processes in the literature classroom - Lemieux, Amélie; Lacelle, Nathalie (Language & literacy Canadien Online Journal, 2016)

Mapping Holistic Learning: An Introductory Guide to Aesthetigrams - White, Boyd; Lemieux, Amélie (Peter Lang, 2017)
Mapping Holistic Learning: An Introductory Guide to Aesthetigrams introduces the concept of aesthetigrams. These are participant-produced visual maps of aesthetic engagement. The map-making strategy was originally developed by one of the authors, Boyd White, to assist him in understanding what his university-level students were experiencing as they interacted with artworks. Such interactions are, after all, private, individualistic, and fleeting. How can a teacher foster student/teacher dialogue that might lead to enhanced engagement, much less do research, without a concrete record of such engagement? Aesthetigrams provide that record. Recently, the strategy has been adapted to other fields of study—the teaching of literature, and philosophy for children, as well as the writing of poetry. Boyd White and Amélie Lemieux are persuaded that the strategy could be expanded into other disciplines. For example, might it not be useful for a teacher to know what a student is feeling and thinking as she struggles with a mathematical concept? Mapping Holistic Learning is divided into three sections. Chapter 1 addresses the theoretical framework that underpins the authors’ research. The second section, Chapters 2 to 5, provides examples of aesthetigram usage within the formal education environment, in art and literature classrooms. The third section, Chapters 6 and 7, introduces two recent experiments in informal settings—one in an adult poetry workshop, the other in a philosophy-for-children workshop. It is not necessary to follow the book in chronological order. Readers are invited to attend to the chapters that most closely address their individual interests.

Sur la notion d’engagement envers la lecture : Constats, angles morts et complexités - Lemieux, Amélie; Berthiaume, R. (Nexus, 2023)

Éclosions in literacy research: Rereading Brandt and Clinton's “Limits of the local” - Ferguson, D.; Lemieux, Amélie (Journal of Literacy Research, 2022)

When in doubt, map it out: Teachers’ digital storytelling researched through documentation - Lemieux, Amélie; Mason, S. (Canadian Journal of Learning and Technology, 2022)

W(e)aving: When maker literacies and diffraction collide - Lemieux, Amélie; Thériault, V. (Studies in the Education of Adults, 2021)

On the relational autonomy of materials: Entanglements in maker literacies research - Lemieux, Amélie; Rowsell, Jennifer (Literacy, 2020)

Digital technologies and online learning in secondary education - Lemieux, Amélie; Rowsell, Jennifer (Bloomsbury Education and Childhood Studies, 2019)

Mobilizing students’ interpretive resources: A novel take on subjective response in the literature classroom - Lemieux, Amélie; Lacelle, Nathalie (Language and Literacy, 2016)

Reflecting selves: Pre-service teacher identity development explored through material culture - White, B.; Lemieux, Amélie (LEARNing Landscapes, 2015)

Dis/comforting shelfies: Travelling literacies other-wise in disrupted times. - Scott, F.; Lemieux, Amélie; Johnston, K (Digital Culture & Education, 2022)

À l’aube de la transmédialité : de l’oeuvre antérieure comme péritexte - Lemieux, Amélie (Péritexte et transmédialité, 2023)

Exploring the arts and literacy in curriculum: A cross-cultural comparison of Australia, Canada and France - Barton, G.; Lemieux, Amélie; Chabanne, Jean-Charles (Australian Art Education, 2018)

Dismantling X-Men Apocalypse: The spaces between transmedia storytelling and transmedia characters - Lemieux, Amélie (Transmédialité, bande dessinée et adaptation, 2019)

Working towards more socially just futures: Five areas for transdisciplinary literacies research - Lemieux, Amélie; Boyle, L.; Simmonds, E.; Rahm, J. (Literacy, 2023)

Visualizing mapping as pedagogy for literacy futures - Lemieux, Amélie; Smith, A.; McLean, C.; Rowsell, Jennifer (Journal of Curriculum Theorizing, 2020)

Crafting stories and cracking codes in a Canadian elementary school - Lemieux, Amélie; Rowsell, Jennifer (Maker Literacies and Maker Identities in the Digital Age: Learning and Playing through Modes and Media, 2021)

Pedagogies of empathy-building: Canadian and Azorean perspectives of film-viewing in higher education - Lemieux, Amélie; Burkholder, C. (Compassion and Empathy in Educational Contexts, 2019)

Maker research: A proposition of thinking-with maker culture as slow scholarship - Sinner, A.; Lemieux, Amélie (Connection-Contact-Community, 2021)

Artful portable library spaces: Increasing community agency and shared knowledge - Lemieux, Amélie; McLarnon, M. (Canadian Curriculum Studies: A Métissage of Inspiration/Imagination/Interconnection, 2018)

Entre histoire et fiction: la Rébellion des Patriotes en roman et en bande dessinée pour la jeunesse québécoise - Lemieux, Amélie; Guénette, M.-F. (Fictions historiques pour la jeunesse en France et au Québec, 2016)

Intra-active entanglements: What posthuman and new materialist frameworks can offer the learning sciences - Sheridan, M. P.; Lemieux, Amélie; Do Nascimento, A.; Arnseth, H. C. (British Journal of Educational Technology, 2020)

The stuff that heroes are made of: Elastic, sticky, messy literacies in children's transmedial cultures - Rowsell, Jennifer; Lemieux, Amélie; Swartz, L.; Burkitt, J.; Turcotte, M. (Language Arts, 2018)

Defining artful literacies : Adolescent affects, belonging and cross-sectorial creativity - Lemieux, Amélie; Beaton, E. (Art Education in Canadian Museums: Practices in Action, 2024)

‘This Documentary Actually Makes Welland Look Good’: Exploring Posthumanism in a High School Documentary Film Project - Lemieux, Amélie; Rowsell, Jennifer (Transforming Language and Literacy Education: New Materialism, Posthumanism, and Ontoethics, 2020)

18e séminaire de recherche en littératie médiatique multimodale | LMM - Brunel, Magali; Boutin, Jean-Francois; Coste, Jimmy; Lalonde, Martin; Lemieux, Amélie; Audet, René (2021)

InstaPoésie : de l’espace de partage littéraire virtuel à la production de textes poétiques en classe du secondaire - Lemieux, Amélie; Barton, G.; Lewkowich, D.; White, B.; Gauthier, M.-C.; Beauchamp, F. (Revue de recherches en littératie médiatique multimodale, 2022)

Diff/reading data through pedagogies of the other-wise - Lemieux, Amélie; Johnston, K; Scott, F. (Unsettling Literacies: Directions for Literacy Research in Precarious Times, 2022)

Taking a wide-angled view of contemporary digital literacy - Lemieux, Amélie; Rowsell, Jennifer (The Routledge Handbook of Digital Literacies in Early Childhood, 2020)

4e SÉMINAIRE D’ÉTUDE EN LITTÉRATIE MÉDIATIQUE MULTIMODALE, Montréal, 4 avril 2014 | LMM - Boutin, Jean-Francois; Bégin, Mathieu; Majeau, Claude; Lacelle, Nathalie; Lemieux, Amélie; Godin, Geneviève; St-Pierre, René (2014)

On recruiting aesthetic experience: A trioethnography of the affordances and limitations of teaching (with) the arts and literature in a pandemic year - White, B.; Lemieux, Amélie; Émond, Anne-Marie (Making Connections in and through Arts-based Educational Research, 2023)

3e SÉMINAIRE D’ÉTUDE EN LITTÉRATIE MÉDIATIQUE MULTIMODALE, Montréal, 6 décembre 2013 | LMM - Mercier, Jean-Pierre; Faucher, Christine; Lemieux, Nathalie; Lemieux, Amélie; Boutin, Jean-Francois; Richard, Moniques; Lacelle, Nathalie; Lemerise, Suzanne; Lieutier, Prune; St-Pierre, René (2013)

Éduquer à la littératie numérique: communication, culture et création. - Lacelle, Nathalie; Acerra, Eleonora; Audet, René; Boutin, Jean-Francois; Brehm, Sylvain; Gervais, Bertrand; Lalonde, Martin; Mercier, Jean-Pierre; Martel, Virginie; Richard, Moniques; Lemieux, Amélie; Guichon, Nicolas; et al. (Fonds de Recherche du Québec - Société et culture, 2020)

Metaphysics of embodied schooling – The school bus symposium: A poetic journey of co-created conference space - McLarnon, M.; Wiebe, S.; Richardson, P.; Balsawer, V,; Binder, M.; Browning, K.; Conrad, D.; Fels, L.; Gouzouasis, P.; Human, A.; Kim, A.; Leggo, C.; et al. (Art Research International: A Transdisciplinary Journal, 2016)

20e séminaire en LMM ... sortez vos paillettes! | LMM - Boutin, Jean-Francois; Amélie Lemieux; Blanchette, Karine; Lalonde, Martin; Vallières, Amélie; Dumoulin, Pierre-Gabriel; Mahieu, Luc; Gladu, Eve; Martel, Virginie; Lacelle, Nathalie; Audet, René; Lahouste, Corentin; et al. (2022)